A durable and robust Fe–N–C electrocatalyst for oxygen reduction reactions by introducing Ti3C2–TiO2 as radical scavengers. (12th February 2023) - Gu, Wenling; Xu, Jianbo; Sun, Jing; Zhao, Tianshou
Abstract: Modern Fe–N–C electrocatalysts are promising as alternatives to expensive Pt-based catalysts for oxygen reduction reactions (ORR). Although the activity of this type of electrocatalyst have been improved over the years, their durability and longevity need critical enhancements for practical applications in fuel cells. Typically, the incomplete oxygen reduction inevitably generates reactive oxygen species, including ·OH and HO2 · radicals, which will fiercely attack the carbon support and directly damage active sites in Fe–N–C electrocatalysts. Herein, a durable and robust Fe–N–C@Ti3 C2 –TiO2 electrocatalyst for high-efficiency ORR is synthesized, in which Ti3 C2 –TiO2 could effectively scavenge ·OH radicals or decompose H2 O2 molecules, and synergistically work with Fe–N–C catalysts to improve the durability. Consequently, the Fe–N–C@Ti3 C2 –TiO2 electrocatalyst shows prominent ORR performance in both alkaline and acidic electrolytes, low H2 O2 yield, and long-term stability. This work provides great prospects for the design of highly stable ORR electrocatalysts by introducing radical scavengers as an active defense to proactively eliminate H2 O2 and its radicals. Highlights: A durable and robust Fe–N–C@Ti3 C2 –TiO2 catalyst for ORR was synthesized due to the synergy between Ti3 C2 –TiO2 and Fe–N–C. Ti3 C2 –TiO2 could effectively scavenge ·OH radicals or decompose H2 O2 molecule to enhance the durability. The as-prepared catalyst exhibits excellent ORR catalytic activity in both alkaline and acidic electrolytes. This work provides great prospects for designing stable ORR catalysts by using radical scavengers as active defense.